Log Data Structure for Illegal Logging Tracking System - Ilham Nugraha, Yunanta; Andriana Mutiara, Giva; Handayani, Rini (International Journal of Engineering and Technology, 2018)
Forest is a natural ecosystem that plays an important role in human life. Unfortunately, due to the exploitation of the forest wealth, the forest ecosystem becomes increasingly diminished. One of the most significant forest damages caused by illegal logging. In some cases, sometimes the information about log harvest that obtained from the logging area always has a discrepancy. To reduce the cunning which is done by the perpetrators, however, a system that can track and monitor the log position from a remote area is needed. This system using APC220 as a WSN using Star topology, embed with RFID reader and Arduino Uno. By designing a log data structure, the tracking and monitoring log is possible to build. This system was testing by three scenarios. The log data structure can be interpreted 100% by the system. According to the resulting test, it can be concluded that this system can track down the position of the log, and inform the forest patrol officer the predictable place where the log is missing.